A SnRK2-HAK regulatory module confers natural variation of salt tolerance in maize - Ming Zhang; Xueyan Zhou; Limin Wang; Xiaoyan Liang; Xin Liu; Caifu Jiang (Nature Communications)
Abstract The exclusion of sodium ions (Na+) from the shoot tissue, termed shoot Na+ exclusion, underlies a core mechanism of crop salt tolerance. Recent studies have shown that the HAK (High-Affinity K+ Transporter) family Na+ transporters play a key role in shoot Na+ exclusion of various crops, however, it is unknown whether and how this type of transporter is post-transcriptionally regulated. Here, we show that two closely related SnRK2 kinases, designated as ZmSnRK2.9 and ZmSnRK2.10, promote shoot Na+ exclusion and salt tolerance by activating the Na+ transporter ZmHAK4 in maize. Under salt conditions, the kinase activity of ZmSnRK2.9 and ZmSnRK2.10 is activated, then they interact with and phosphorylate ZmHAK4 at Ser5, increasing the Na+ transport activity of ZmHAK4, which in turn promotes salt tolerance by improving the exclusion of Na+ from the shoot tissue. Furthermore, we show that a 20-bp deletion that occurred naturally in the ZmSnRK2.10 promoter decreases its transcript level, resulting in an increased shoot Na+ content under salt conditions. Our findings support a breeding program that can utilize the favorable alleles of ZmHAK4 and ZmSnRK2.10 to enhance both the transcriptional and post-transcriptional activation of ZmHAK4, thus advancing the development of salt-tolerant maize.